Blocos cimentícios produzidos com a incorporação de fibras de coco e resíduos de quartzito - Terra, Isabelle Cristine de Carvalho (2018)
The search for new materials aimed at the use of waste is one of the themes of current research. Thus, the use of waste, minerals, or agroindustrial in the construction sector is an environmentally correct. The objective of this work was to evaluate the use of the quartzite residue as a substitute for sand and the addition of coconut fibers as a substitute for stone powder in the production of masonry blocks. It was evaluated the substitution of 0%, 25%, 50%, 75% and 100% of the sand by the quartzite residue, with or without the insertion of 2.5% of coconut fiber in relation to the volume of stone powder . The quartzites were evaluated for their granulometry, chemical composition and pozolanicity. The coconut fibers were evaluated according to their chemical properties and their inhibition of cement cure. The blocks were made in a vibratory machine and an initial dosage of 8.2% of CPV-ARI cement, 45.9% sand, 45.9% stone powder and 8.8% water. After production, the blocks were kept at room temperature for 28 days to perform the cure. Subsequently the blocks were submitted to characterization of the physical, mechanical and thermal properties. After analysis the quartzite residue was characterized as a rich material in silicon, and predisposed to be pozzolanic, which makes it favorable for use in cementitious matrices. Coconut fiber in relation to its chemical properties and inhibition of cement cure resulted in its low percentage of extractives and low inhibition index, will eventually affect cement solidification in a reduced manner. The final results of the blocks indicate that the increase of the quartzite content incorporated in the concrete, as well as its physical properties, there was an increase in the voids index and the water absorption values of the blocks, reduction of the apparent density, and the thermal conductivity their values reduced, while for the mechanical property of compressive stre ngth, values were increased with the use of 25% of the quartzite residue. The addition of coconut fiber reduced the average thermal conductivity of the concrete produced, which provides important reflexes for the performance of the blocks as to the therm al comfort of the built environments. Consequently, the use of quartzite and coconut fiber in masonry blocks is a viable technique that has led to the creation of a new product with adequate characteristics and an option for appropriate disposal of these mineral and agroindustrial residues.